A new reverse engineering method to combine FEM and CFD simulation three-dimensional insight into the chipping zone during the drilling of Inconel 718 with internal cooling. Issue 6 (2nd November 2018) - Oezkaya, Ekrem; Biermann, Dirk
ABSTRACT: The use of cooling lubricants in metal machining increases both the tool life and the quality of workpieces and improves the overall sustainability of production systems. In addition to fulfilling these main functions, the focus of machining processes is also related to the reduction of environmental pollution. This can for example be achieved by an optimized arrangement of the cutting tool cooling channels. Therefore, the active cutting edges of the tool should be effectively supplied with a sufficient amount of cooling lubricant. An analysis of the tribological stress is rather difficult because the complex contact zone is inaccessible. Hence, optical investigations are often limited to only observing the chip formation or analyzing the process without considering the influence of the chips. This article presents an innovative method, which enables a deeper three-dimensional insight into the chip formation zone during drilling with internal cooling channels, considering the cooling lubricant distribution and chip formation. The chip formation simulation based on the finite element method and the computational fluid dynamics flow simulation are combined. In this way, the differences between the different geometric models that do not allow any joint generation of numerical information due to missing interfaces are overcome.